Membangun Reputasi Pendidikan Dasar Islam Melalui Public Relation di Era Revolusi Industri 4.0 (Studi pada Sekolah Dasar Islam Terpadu di Kabupaten Bekasi) - Nurdin Rivaldy; Ilzamudin Ma’mur; Rijal Firdaos (STAI Terpadu Yogyakarta, 2023)
Building Public Relations in primary Islamic education requires a reputation that builds interest in Public Relations with prospective students, parental trust, and community support, whereas the era of the industrial revolution 4.0 demands technology Public Relations improve broader. This study aims to explain SDIT ALFIDAA's efforts to build a reputation through public relations through social media in the era of the industrial revolution 4.0. This research uses a qualitative with a case study method at an integrated Islamic elementary school (SDIT) in ALFIDAA Bekasi, West Java. Data collection used interviews, observation, and documentation. The data analysis uses content analysis. The research results show that Public Relations as digital information through social media, namely Instagram and Facebook, build a school's reputation and a unified communication strategy. Public Relations builds the school's reputation by managing and addressing issues, responding quickly and transparently through social media, providing assistance, and contacting those involved. Overcome the school's reputation's negative impact by actively building community trust with social media. The research contribution effectively uses Public Relations to maintain and enhance the school's reputation. The research implications show that the more significant the role of Public Relations, the better it is for the community, increasing the school’s reputation.